Vitamin D supplementation during pregnancy and infancy reduces aeroallergen sensitization: a randomized controlled trial. Issue 9 (29th April 2016) - Grant, C. C.; Crane, J.; Mitchell, E. A.; Sinclair, J.; Stewart, A.; Milne, T.; Knight, J.; Gilchrist, C.; Camargo, C. A.
Abstract: Background: Vitamin D has immune‐modulating effects. We determined whether vitamin D supplementation during pregnancy and infancy prevents aeroallergen sensitization and primary care respiratory illness presentations. Methods: A randomized, double‐blind, placebo‐controlled parallel‐group trial. We assigned pregnant women, from 27‐week gestation to birth, and then their infants, from birth to 6 months, to placebo or one of two dosages of daily oral vitamin D. Woman/infant pairs were randomized to: placebo/placebo, 1000 IU/400 IU or 2000 IU/800 IU. When the children were 18 months old, we measured serum‐specific IgE antibodies and identified acute primary care visits described by the doctor to be due to a cold, otitis media, an upper respiratory infection, croup, asthma, bronchitis, bronchiolitis, a wheezy lower respiratory infection or fever and cough. Results: Specific IgE was measured on 185 of 260 (71%) enrolled children. The proportion of children sensitized differed by study group for four mite antigens: Dermatophagoides farinae (Der‐f1, Der‐f2) and Dermatophagoides pteronyssinus (Der‐p1, Der‐p2). With results presented for placebo, lower dose, and higher dose vitamin D, respectively (all P < 0.05): Der‐f1 (18%, 10%, 2%), Der‐f2 (14%, 3%, 2%), Der‐p1 (19%, 14%, 3%) and Der‐p2 (12%, 2%, 3%). There were study group differences in the proportion of children with primary care visits described by the doctor as being for asthma (11%, 0%, 4%, P = 0.002), but not for the other respiratory diagnoses. Conclusions: Vitamin D supplementation during pregnancy and infancy reduces the proportion of children sensitized to mites at age 18 months. Preliminary data indicate a possible effect on primary care visits where asthma is diagnosed.